Why moralize upon it? democratic education through American literature and film - Danoff, Brian (Politics, literature, & film., 2020)
Danoff argues that novels and films with an ambiguous, nuanced, and tragic outlook help teach citizen-readers how to think through the moral complexities of political issues on which they must render judgment. He claims that some of the most profound American thinking about the nature of democratic leadership has come through works of fiction.